The lower limit of thermal conductivity in multicomponent solutions of rare gas solids - Konstantinov, V.A.; Karachevtseva, A.V.; Revyakin, V.P.; Sagan, V.V. (Физика низких температур, 2019)
The isochoric thermal conductivity of Kr₀.₆₃Xe₀.₃₇ solid solution has been investigated for three samples with different molar volumes in the temperature range from 80 K to the onset of melting, as well as the thermal conductivity of the ternary (Kr₀.₆₃Ar₀.₁₈₅Xe₀.₁₈₅) and quaternary (Kr₀.₆₃Ar₀.₁₂Xe₀.₁₂(CH₄)0.₁₃) solid solutions. It is found that for multi-component alloys, the thermal conductivity reaches a minimum, whereby adding more impurity atoms in the solid solution does not affect the thermal conductivity in agreement with the recent nonequilibrium molecular dynamics calculations for argon. The phonon contribution to the total thermal conductivity depends significantly on molar volume of sample and impurity concentration, in contrast to the contribution of diffusive modes, which is practically independent of these factors.